Digital civic engagement: transforming the model of citizen involvement in the digital democracy era - Suganda, Fadhila Aqilahawwa; Sundawa, Dadang; Budimansyah, Dasim; Sari, Mulia (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
The development of digital technology has brought fundamental changes in democratic practices and patterns of citizen involvement. This article aims to analyze digital civic engagement as a form of citizen involvement and the transformation from conventional to digital models in the context of Indonesian democracy. The study focuses on changes in the form of civic engagement; the role of social media and digital platforms as new public sphere; the challenges and opportunities of digital civic engagement; and implications for civic education. This article uses a qualitative approach, with a literature review and a conceptual analysis of relevant previous research, contextualized within the dynamics of democracy in Indonesia. The results of the study indicate that digital civic engagement offers opportunities to expand citizen involvement in a more inclusive, rapid, and interactive manner, especially for the younger generation. However, digital civic engagement practices also pose serious challenges, including the spread of disinformation, political polarization, low digital literacy, and a decline in the quality of public deliberation. This article also emphasizes that the transformation of civic engagement in the digital era has important implications for civic education. Civic education needs to adapt by integrating digital literacy, digital citizenship ethics and by strengthening citizens' critical thinking capacity. Thus, digital civic engagement is not only a means of political expression, but also contributes to strengthening the quality of democracy.